We Shall Not Be Moved/No nos moverán - Spener, David, 1961- (Book collections on Project MUSE., 2016)
We Shall Not Be Moved: The Trail Blazed by a Song from the U.S. South to Spain and South America details the history of "We Shall Not Be Moved" from its birth as a slave spiritual in the U.S. South and its subsequent adoption as a standard hymn by the U.S. labor, civil rights, and farmworker movements, to its singing in the student movement opposing the Franco dictatorship in Spain in the 1960s, and finally to its arrival in the South American country of Chile during its experiment with democratic socialism in the early 1970s. The book outlines the role the song has played in each of the movements in which it has been sung and analyzes its dissemination, function, and meaning through a number of different sociological and anthropological lenses.